1993
DOI: 10.1182/blood.v82.7.2261.2261
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 in paraneoplastic thrombocytosis [letter]

Abstract: Interleukin-6 (IL6) is able to stimulate thrombopoiesis in vitro and in vivo in murine and primate models.',' A phase I trial of recombinant IL-6 in humans has demonstrated the capacity of this cytokine for increasing platelet counts in vivo.' However, the physiologic role of IL-6 in the regulation of thrombopoiesis remains unclear." Increased serum IL-6 levels have been reported in patients with reactive thrombocytosis but the causative role of IL-6 for thrombocytosis has not been e~tablished.~ We report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Secondary or reactive thrombocytosis occurs in several clinical conditions, including various malignancies [4]; it also occurs in patients with metastatic RCC [5]. We observed that some patients with thrombocytosis and metastatic RCC had a shorter life expectancy than those with a normal platelet count.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Secondary or reactive thrombocytosis occurs in several clinical conditions, including various malignancies [4]; it also occurs in patients with metastatic RCC [5]. We observed that some patients with thrombocytosis and metastatic RCC had a shorter life expectancy than those with a normal platelet count.…”
Section: Introductionmentioning
confidence: 67%
“…They noted a 65% 5-year survival rate in patients with a normal platelet count, whereas those patients with thrombocytosis had a 5-year survival rate of only 25%. Only recently have Blay et al [5] noted thrombocytosis associated with metastatic RCC in their studies of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cytokines produced by malignant cells, such as interleukin-6 and colony stimulating factors (17)(18)(19), are associated with thrombocytosis. These cytokines are also produced by ovarian cancer (17'2°-22).…”
Section: Discussionmentioning
confidence: 99%
“…10 The reactive THC and CRP elevation in RCC are both caused by the production of inflammatory cytokines such as IL-6. [11][12][13] When metastatic RCC is treated with IL-2, serum IL-6 levels and CRP levels are correlated and the survival of patients with detectable IL-6 is shorter than that of patients with undetectable IL-6. 14 RCC patients with elevated serum IL-6 frequently have higher platelet counts and higher CRP levels than do those without elevated IL-6, 12 and elevated serum IL-6 elevation is also significantly associated with paraneoplastic THC in patients with RCC.…”
Section: Introductionmentioning
confidence: 99%